Consumer Satisfaction of Chocolate Product and Its Marketing Facilities: Case Study of a MSME Chocolate Factory in Jember - Hartatri, Diany Faila Sophia; Aprilia, Sugesti Dwi (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2022)
The role of micro, small and medium enterprises (MSME)-scale of cocoa agro-industry sector in Indonesia has increased along with the increasing number of MSMEs engaged in secondary cocoa processing sector. One of the factors that influence the sustainability of cocoa agroindustry business is customer satisfaction index (CSI). Therefore, this study aims to analyze consumer satisfaction index of chocolate product and its marketing facilities offered by producer which can then be used as input for the development of chocolate business. This research was conducted at MSME chocolate factory located in Jember, Indonesia. The selection of this location was done purposively with the consideration that the MSME chocolate factory produces couverture chocolate products. The research method chosen is descriptive using the analysis method of customer satisfactionindex (CSI) and importance performance analysis (IPA). There were 96 respondents involved in this research. Determination of sample size was calculated by using the Slovin formula. The results showed that the majority of the chocolate consumers are, young generation female who have well literacy of digital experiences. Furthermore, CSI of chocolate products and its marketing facilities was 77.86%, which indicates that overall consumers were satisfied. Several attributes that has satisfied the consumers are chocolate taste, packaging, chocolate shape, food safety guarantees labeled at the chocolate products, outlet cleanliness, outlet convenience, the atmosphere offered by the outlet, friendliness of the salesperson to the customer, salesperson’s knowledge of the menu, responsiveness of salespeople in fulfilling orders, attractive outlet interior design, cleanliness and availability of toilets, prayer rooms and supporting facilities for consumer comfort has also satisfied the consumers. Priority improvement strategies that require to be conducted to increase consumer satisfaction include adjusting the price of chocolate products, increasing promotions through social media and providing entertainment facilities, such as music, wi-fi, and TV at chocolate marketing facilities.